Effluent Tenascin-C Levels Reflect Peritoneal Deterioration in Peritoneal Dialysis: MAJOR IN PD Study. (6th December 2015) - Hirahara, Ichiro; Kusano, Eiji; Imai, Toshimi; Morishita, Yoshiyuki; Inoue, Makoto; Akimoto, Tetsu; Saito, Osamu; Muto, Shigeaki; Nagata, Daisuke
Abstract : Peritoneal deterioration causing structural changes and functional decline is a major complication of peritoneal dialysis (PD). The aim of this study was to explore effluent biomarkers reflecting peritoneal deterioration. In an animal study, rats were intraperitoneally administered with PD fluids adding 20 mM methylglyoxal (MGO) or 20 mM formaldehyde (FA) every day for 21 days. In the MGO-treated rats, tenascin-C (TN-C) levels in the peritoneal effluents were remarkably high and a cluster of TN-C-positive mesothelial cells with epithelial-to-mesenchymal transition- (EMT-) like change excessively proliferated at the peritoneal surface, but not in the FA-treated rats. Effluent matrix metalloproteinase-2 (MMP-2) levels increased in both the MGO- and FA-treated rats. In a clinical study at 18 centers between 2006 and 2013, effluent TN-C and MMP-2 levels were quantified in 182 PD patients with end-stage renal disease. Peritoneal function was estimated using the peritoneal equilibration test (PET). From the PET results, the D/P Cr ratio was correlated with effluent levels of TN-C ( ρ = 0.57, p < 0.001 ) and MMP-2 ( ρ = 0.73, p < 0.001 ). We suggest that TN-C in the effluents may be a diagnostic marker for peritoneal deterioration with EMT-like change in mesothelial cells in PD.